2016
DOI: 10.1016/j.jpsychires.2016.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Duration of untreated psychosis: Impact of the definition of treatment onset on its predictive value over three years of treatment

Abstract: We wish to thank the case managers from the Tipp Program for their invaluable work for collecting this data over the years. We also express our gratitude to all patients for their enduring participation. The authors have declared that there are no conflicts of interest in relation to the subject of the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 33 publications
3
26
1
Order By: Relevance
“…A recent study investigating differences in outcome based on onset of either medical treatment, SEI treatment, or both combined indicated that the beneficial impact of short DUP on outcome was strongest if the end of DUP was defined as both adequate medical treatment and enrollment in a SEI program. 24 Our finding of an effect on the negative symptoms for participants with a total treatment delay of <6 months support the notion that adequate treatment for patients with newly diagnosed schizophrenia should be considered both medical treatment and psycho-social treatment.…”
Section: Discussionsupporting
confidence: 72%
“…A recent study investigating differences in outcome based on onset of either medical treatment, SEI treatment, or both combined indicated that the beneficial impact of short DUP on outcome was strongest if the end of DUP was defined as both adequate medical treatment and enrollment in a SEI program. 24 Our finding of an effect on the negative symptoms for participants with a total treatment delay of <6 months support the notion that adequate treatment for patients with newly diagnosed schizophrenia should be considered both medical treatment and psycho-social treatment.…”
Section: Discussionsupporting
confidence: 72%
“…Our sample contained 52.2% male patients and we did not find significant differences in the sample by gender. This finding differs from other studies that showed that in non- affective psychosis male patients are represented slightly more (Kvig et al, 2017), (Szöke et al, 2014;Malla et al, 2004), and there is a reported odds ratio of 2.37 for nonaffective psychosis patients being male (Golay et al, 2016).…”
Section: Discussioncontrasting
confidence: 99%
“…The second strand of evidence is a large body of research on the deleterious long-term effects of a long DUP. Although there may be alternative explanations for this association (eg, long DUP may reflect particularly severe presentations), and the empirical evidence has been constructed with studies of variable methodology (Polari et al, 2011), the signal has been remarkably consistent and it is improved when treatment onset is defined more stringently, including by requiring adequate antipsychotic adherence (Golay et al, 2016). Comprehensive meta-analyses indicate that the longer the DUP, the worse patients fare clinically and functionally, both in the short-term (Perkins, Gu, Boteva, & Lieberman, 2005) and the long-term (Penttila et al, 2014).…”
Section: Discussionmentioning
confidence: 99%